Implikasi PMK-37 Tahun 2025 terhadap Keseimbangan Fiskal dan Daya Tahan UMKM - Muan Ridhani Panjaitan (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This study aims to examine the implications of Minister of Finance Regulation (PMK) Number 37 of 2025 on the national fiscal balance and the resilience of micro, small, and medium enterprises (MSMEs) in the context of the rapid development of e-commerce in Indonesia. This PMK introduces a collect at the source mechanism, which is the appointment of certain marketplaces as collectors of Income Tax (PPh) Article 22 on online merchant transactions. This policy is seen as one of the strategic steps to expand the digital tax base, improve fiscal efficiency, and support the principle of compliance by design. The research uses a descriptive qualitative approach through documentation studies of official government documents, academic literature, and relevant publications. The results of the study show that the implementation of PMK 37/2025 has the potential to have a positive impact on state revenue through digital taxation optimization. In addition, this policy can strengthen the fiscal balance by minimizing the potential for tax avoidance in the growing digital economy sector. However, on the other hand, the policy also poses a number of challenges for MSMEs, especially related to administrative readiness, limited fiscal literacy, and adaptability to the tax digitalization system. For most MSMEs, additional tax liabilities can be a burden that affects cash flow, competitiveness, and business sustainability, especially for MSMEs that are still in the growth stage and have limited resources. The policy implications identified include the importance of improving fiscal education and literacy programs, the development of user-friendly digital reporting systems, and active collaboration between fiscal authorities, marketplaces, and MSME actors. Thus, the success of the implementation of PMK 37/2025 is not only determined by regulations, but also by the extent to which the policy is able to be implemented in an inclusive, adaptive, and sustainable manner in supporting national economic development.